Potential role of pharmacogenomics testing in the setting of enhanced recovery pathways after surgery - Awad H; Ahmed A; Urman RD; Stoicea N; Bergese SD (Dove Medical Press, 2019)
Hamdy Awad,1 Ahmed Ahmed,2 Richard D Urman,3 Nicoleta Stoicea1,4, Sergio D Bergese1,51Department of Anesthesiology, The Ohio State University Wexner Medical Center, Columbus, OH, USA; 2Department of Anesthesiology, The University of Texas, Houston, TX, USA; 3Department of Anesthesiology, Perioperative and Pain Medicine, Brigham and Women’s Hospital, Harvard Medical School, Boston, MA, USA; 4Department of Biological Chemistry and Pharmacology, The Ohio State University Wexner Medical Center, Columbus, OH, USA; 5Department of Neurological Surgery, The Ohio State University Wexner Medical Center, Columbus, OH, USAAbstract: In 2001, a group of European academic surgeons created the Enhanced Recovery After Surgery (ERAS) study group and established the first official ERAS protocol. One of the most significant challenges during ERAS implementation is variability of drugs used throughout the perioperative period. Pharmacogenomic testing (blood or saliva) results (obtained within approximately 48 hrs) provide guidelines on how to prescribe the optimal drug with the optimal dosage to each patient based on an individual’s unique genetic profile. Pharmacogenomic testing of various methods of multimodal analgesia is an essential element of ERAS protocols spanning the entire perioperative period to ultimately optimize postoperative pain control. The key goal for anesthetic management in ERAS protocols is to facilitate rapid emergence by using the shortest acting agents available, thus accelerating recovery and reducing length of stay, hospital expenses, and postoperative complications. Postoperative nausea and vomiting (PONV) is an additional challenge that should be overcome to ensure an enhanced recovery and shorter length of stay with the use of antiemetics. Postoperative ileus (POI) can result in longer hospital stay with increasing susceptibility to associated morbidities along with an increase in associated hospitalization costs. Genetics-guided pharmacotherapy and its impact on clinical outcomes should be thoroughly studied for better understanding and managing drug administration in the settings of ERAS.Keywords: pharmacogenomics, perioperative outcome, pharmacogenomics testing, Enhanced Recovery After Surgery